MAIN PROBLEMS OF ATTRACTION OF OWN AND LOAN MEANS AT THE ENTERPRISE IN THE CONDITIONS OF FINANCIAL INSTABILITY - Tasmaganbetov Aslan; Ataniyazov Zhumabay; Аgleshov Каnаt (Academic Journal of Physical and Chemical Sciences, 2020)
The financial condition of the enterprise largely depends on what funds it has at its disposal and where they are invested. The need for equity is due to the requirements of self-financing enterprises. Equity is the basis of the independence of enterprises. Currently, the guarantee of the normal process of expanded reproduction is the financing of capital investments through borrowing. The results of the analysis of financial stability are also not satisfactory. For financial stabilization of the enterprise it is necessary to provide long-term financial balance in the course of the forthcoming economic development. In accordance with this, it was proposed to increase financial stability to attract borrowed capital for a long-term period in order to reduce short-term liabilities of the enterprise, namely cash in the amount of thousands of tenge for current lease payments. As a result of this event, the liquidity of the balance sheet and the maneuverability of capital will increase. As a result, the company’s management decided to develop measures to improve the efficiency of the use of borrowed funds. Debt management is an integral part of financial management at the enterprise, actively used for financial planning and development of financial strategy of the enterprise.